KEPATUHAN MASYARAKAT TERHADAP PEMBAYARAN PAJAK BUMI DAN BANGUNAN DIHUBUNGKAN DENGAN TINGKAT KESEJAHTERAAN MASYARAKAT - Naib Naib (Pamulang Law Review, 2018)
Abstract The aimed for knowing the relation between the grade of people welfare with the obedient for paying of land and building tax and for knowing some problem which arise from the great happening of tax climbing and for knowing the steps which have necessary done according to increase the people abeident facing to the tax payment. The method which I have done in this is descriptive method. Collecting data is done by field observation, the writer had arranged by direct interviewing to the people, ravine groups and sub district groups, for knowing the real situation, in order to become as the collecting data and analysis. Library examination, the writer have collected from some books which related and the regulations to become the developing writing which having concrete data’s. The result of this examination had desribed, that the fetching tax quite succeeded, as well as the government hoped, that is the people can be put into 95% category had paid the tax this caused which the grade of obedient and people morality guite high, so the low people economy and high people economy in paying, there are no problems, even though the situation of Indonesia economy today is very concerned.